The Effect of Mineral Water Packaging Designs on Level of Consumer Decision in Purchase - Dr. Prayanto Widyo Harsanto, M.Sn.; Jalung Wirangga Jakti (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
Abstract The function of packaging is to wrap or protect a product. It has a role in informing various things related to a product, such as the type of product, product quality, benefits, and product image. Through packaging design, consumers are also assured that the packaged products are more secure, healthy, and safe. Excellent and attractive packaging design can foster positive consumer perceptions of the product. This positive perception of consumers can have an impact on certain decisions on consumers. The emergence of various mineral water bottle brands is currently causing intense competition to win the hearts of consumers. Various ways have been made to attract consumer interest, one of which is through packaging design. Packaging design is considered one of the ways to shape perceptions and improve consumer decisions to buy. Besides, the perceptions that have been formed can help improve or decrease the brand image. This study aims to determine consumer perceptions of the form of mineral water packaging design marketed in Indonesia. Through this research, the information will be obtained that can be used as a reference regarding packaging design and to determine consumer perceptions of purchasing decisions for a product. The method used in this research is a qualitative method, supported by quasi data (quantitative experimental) with an aesthetic approach (design). Through packaging design elements such as color, shape, brand, and logo, illustration, and typography will form perceptions in the minds of consumers regarding the suitability of the product with the packaging. Thus, packaging design has the power to introduce products to consumers, help improve purchasing decisions, and can provide correlated value to form a brand image in the eyes of consumers. Pengaruh Desain Kemasan Air Mineral terhadap Tingkat Keputusan Konsumen dalam Pembelian Abstrak Fungsi kemasan tidak hanya untuk membungkus atau melindungi sebuah produk, tetapi juga berperan mengomunikasikan/menginformasikan berbagai hal terkait dengan sebuah produk, seperti jenis produk, kualitas produk, manfaat, dan citra sebuah produk. Melalui desain kemasan pula konsumen diyakinkan bahwa produk yang dikemas lebih terjamin keamanan, kesehatan, dan keselamatannya. Desain kemasan yang baik dan menarik dapat menumbuhkan persepsi positif konsumen terhadap produk. Persepsi positif konsumen ini dapat berdampak pada keputusan tertentu pada konsumen. Munculnya berbagai merek minuman mineral kemasan saat ini menimbulkan persaingan yang ketat untuk saling merebut hati konsumen. Berbagai cara telah dilakukan untuk menarik minat konsumen/pasar, salah satunya melalui desain kemasan. Desain kemasan dianggap merupakan salah satu cara yang mampu membentuk persepsi dan meningkatkan keputusan konsumen untuk membeli. Selain itu, persepsi yang telah terbentuk dapat membantu meningkatkan atau menurunkan citra merek suatu produk. Penelitian ini bertujuan untuk mengetahui persepsi konsumen terhadap bentuk desain kemasan minuman mineral yang dipasarkan di Indonesia. Melalui penelitian ini pula akan diperoleh informasi yang dapat menjadi rujukan terkait desain kemasan dan untuk mengetahui persepsi konsumen terhadap keputusan pembelian terhadap suatu produk. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, didukung data quasi (kuantitatif eksperimen) dengan pendekatan estetika (desain). Melalui elemen desain kemasan seperti: warna, bentuk, merek dan logo, illustrasi, dan tipografi akan membentuk persepsi pada benak konsumen mengenai kesesuaian produk dengan kemasan. Dengan demikian, desain kemasan mempunyai kekuatan untuk mengenalkan produk pada konsumen, membantu meningkatkan keputusan pembelian, serta dapat memberikan nilai yang berkorelasi membentuk citra merek di mata konsumen.